MODERN STATE POLICY REALIZATION IN THE FIELD OF THE CULTURE AND DEVELOPMENT IN ADMINISTRATIVE REFORMATION CONDITIONS - Usachenko , A. (Theory and Practice of Public Administration, 2020)
The purpose of the article is to analyze the state policy in Ukraine in the field of culture and identify the development guidelines in the context of administrative reform. The methodology of the research is based on linguistic, complex, system and activity approaches. The linguistic approach is used to define the essence of the concept “state policy”. An integrated approach has allowed to outline the research field. The system approach allowed to reveal the peculiarities of state policy in the field of culture and to formulate development benchmarks in the context administrative reform in Ukraine. Activity approach, which connects goals, tasks, directions of development, allowed to determine the place and spheres of culture in public management processes. The scientific novelty of the work consists in theoretical and methodological substantiation and development of scientific and practical recommendations on the definition of guidelines for the development of the state policy in Ukraine in the field of culture in the context administrative reform. Conclusions. The implementation of the current state policy in the field of culture is carried out in the context administrative reform, which includes certain guidelines for development, in particular: simplification of the management structure, encouragement of inter-sectoral cooperation and inter-ministerial measures, implementation of e-governance tools, separation of administrative processes, etc., in line with the goals and objectives of the State Reform Strategy management for 2016-2020 years.